1999
DOI: 10.1002/(sici)1098-2752(1999)19:4<200::aid-micr7>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tension at the site of coaptation on recovery of sciatic nerve function after neurorrhaphy: Evaluation by walking-track measurement, electrophysiology, histomorphometry, and electron probe X-ray microanalysis

Abstract: The effects of tension at the site of coaptation on recovery of sciatic nerve function after neurorrhaphy were studied by evaluating walking-track measurements, nerve conduction velocity measurements, histomorphometry, and electron probe X-ray microanalysis. Forty adult male Lewis rats underwent right sciatic nerve (SN) transection followed by one of four different nerve repair procedures (N = 10 rats per group). In Group 1, the gap was repaired by end-to-end epineural coaptation. In Group 2, a 5-mm segment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 17 publications
2
13
0
7
Order By: Relevance
“…Though other studies in the primate have found that regeneration under mild tension did not affect the final outcome,45 we found that recovery of the CMAP was slowed when repair was carried out under slight tension (see Fig 3) and the time of reinnervation of the CSAP was delayed (see Fig 6). The adverse effect of tension on regeneration20 may be the result of interference with the blood supply to the nerve,48 and our findings support that even small nerve gaps should be bridged to avoid even modest tension.…”
Section: Discussionsupporting
confidence: 71%
“…Though other studies in the primate have found that regeneration under mild tension did not affect the final outcome,45 we found that recovery of the CMAP was slowed when repair was carried out under slight tension (see Fig 3) and the time of reinnervation of the CSAP was delayed (see Fig 6). The adverse effect of tension on regeneration20 may be the result of interference with the blood supply to the nerve,48 and our findings support that even small nerve gaps should be bridged to avoid even modest tension.…”
Section: Discussionsupporting
confidence: 71%
“…Tensionless coaptation of nerve stumps is known to be inevitable for successful nerve healing [3,4]. However, the recoil of nerve stumps due to debridement or delayed surgical care causes nerve gaps which frequently impede this tensionless nerve repair and remain a great challenge in clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to correct such an imperfection is to anchor epineural stitches at a distance, so as to draw the two stumps closer together and avoid concentrated tension at the nerve suture site itself, displacing all tension to parts further away from the nerve. This suture technique is no novelty, having already been described in several papers 13,14 . The results of the experiment described in this paper showed that regarding motor latency, there was no statistical difference when employing this technique (epineural suture under tension) when compared with the use of grafts.…”
Section: Discussionmentioning
confidence: 48%